Perception of Beneficiary Students of the Free Education Policy: Its Link with Enrollment and Permanence at the Universidad del Bío-Bío - Aguayo Vergara, Margarita (2025)
This study examines the perceptions of students benefiting from Chile’s free tuition policy in higher education, specifically at the Universidad del Bío-Bío. The objective is to understand how this public policy has influenced students’ access to and retention in higher education, based on the experiences of 234 students from six enrollment cohorts between 2016 and 2021. The research is framed within ongoing debates regarding the costs, regulation, and sociodemographic effects of free tuition in Chile. A non-experimental, cross-sectional study was conducted using a questionnaire as the data collection instrument. The questionnaire was developed based on a literature review and validated by a panel of education experts. Descriptive statistics and content analysis were applied, using frequency and percentage calculations with SPSS software (version 23). The findings indicate that respondents positively evaluate the free tuition policy, as it facilitates access to higher education, particularly for students from the most socioeconomically vulnerable sectors. Additionally, the policy has contributed to student retention by reducing financial barriers. However, a significant proportion of female  students have considered dropping out at some point in their academic journey due to factors such as mental health challenges, academic difficulties, vocational concerns, and financial constraints. These findings underscore the need to complement free tuition with additional support measures that enhance student well-being and ease the transition to university life. This study provides empirical evidence on the perceptions of beneficiaries at a public state university in Chile.